2020
DOI: 10.1177/1368430220935974
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive confrontation shapes perceptions and attitudes toward racist content online

Abstract: With more people using social media on a daily basis and the prevalence of racial discrimination online, it becomes imperative to understand what factors impact minority individuals’ perceptions of these transgressions in an online context. Confrontation to discrimination in the form of comments on social media may meaningfully shape perceptions of racism online. Across three studies, we examine how confrontation type (aggressive vs. passive) and confronter group membership (ingroup vs. outgroup) influence Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…In this vein of research, Foster (2015) found that individuals who publicly (vs. privately) tweeted disapproval of sexism reported lower negative affect and greater psychological well‐being. As another example, Meyers et al (2020) found that participants perceive perpetrators’ racist Facebook posts to be more offensive and more likely to report the post to Facebook moderators after reading aggressive (vs. calm) responses to the perpetrator. Meyers et al (2020) also found that participants rated aggressive (vs. calm) Facebook commenters more positively.…”
Section: Discussionmentioning
confidence: 99%
“…In this vein of research, Foster (2015) found that individuals who publicly (vs. privately) tweeted disapproval of sexism reported lower negative affect and greater psychological well‐being. As another example, Meyers et al (2020) found that participants perceive perpetrators’ racist Facebook posts to be more offensive and more likely to report the post to Facebook moderators after reading aggressive (vs. calm) responses to the perpetrator. Meyers et al (2020) also found that participants rated aggressive (vs. calm) Facebook commenters more positively.…”
Section: Discussionmentioning
confidence: 99%
“…Meyers et al (2020) conducted three experiments assessing confrontation of racist comments made online concluding that confronting online racist comments had three positive effects. Participants assessed the racist post as more offensive when an ingroup member aggressively confronted racism.…”
Section: Resultsmentioning
confidence: 99%
“…It is defined as “verbally or nonverbally expressing one’s dissatisfaction with prejudicial and discriminating treatment to the person who is responsible for the remark or behavior” (Ashburn-Nardo & Karim, 2019). Confrontation has been shown to result in prejudice reduction (Meyers et al, 2020). There may be both social and emotional costs in confronting prejudice.…”
Section: Discussionmentioning
confidence: 99%
“…However, confrontations can serve purposes beyond prejudice reduction, such as acting as a coping strategy (Chaney et al., 2015) or promoting norms of egalitarianism more broadly (Czopp et al., 2006; Wellman et al., 2009), suggesting even when people endorse a belief that prejudice is fixed, they may confront for other reasons. e.g., they may cope by using a confrontation style that focuses on one's own experiences with prejudice (e.g., empathy style; Chaney & Sanchez, in press), or use an aggressive confrontation to signal a broader norm (e.g., aggressive confrontations increased perceived offensiveness of act relative to passive confrontations; Meyers et al., 2020).…”
Section: Lay Theories Of Prejudicementioning
confidence: 99%